2007
DOI: 10.1029/2006jg000343
|View full text |Cite
|
Sign up to set email alerts
|

Chemical characteristics of fulvic acids from Arctic surface waters: Microbial contributions and photochemical transformations

Abstract: [1] Dissolved organic matter (DOM) originating from the extensive Arctic tundra is an important source of organic material to the Arctic Ocean. Chemical characteristics of whole water dissolved organic matter (DOM) and the fulvic acid fraction of DOM were studied from nine surface waters in the Arctic region of Alaska to gain insight into the extent of microbial and photochemical transformation of this DOM. All the fulvic acids had a strong terrestrial/higher plant signature, with uniformly depleted d 13C valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

25
230
1
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 198 publications
(257 citation statements)
references
References 44 publications
25
230
1
1
Order By: Relevance
“…Quinone moieties have also been suggested to contribute to humic DOM fluorescence and research has shown that . 50% of DOM fluorescence is potentially due to such structures (Cory and McKnight 2005). Although the exact chemical compounds responsible for DOM fluorescence are still partly undefined, there is much knowledge to be gained about their ecological relevance through tracing their dynamics in the field and laboratory experiments (Baker and Spencer 2004;Cory et al 2007).…”
Section: Fluorescence Characterization Of Dommentioning
confidence: 99%
See 3 more Smart Citations
“…Quinone moieties have also been suggested to contribute to humic DOM fluorescence and research has shown that . 50% of DOM fluorescence is potentially due to such structures (Cory and McKnight 2005). Although the exact chemical compounds responsible for DOM fluorescence are still partly undefined, there is much knowledge to be gained about their ecological relevance through tracing their dynamics in the field and laboratory experiments (Baker and Spencer 2004;Cory et al 2007).…”
Section: Fluorescence Characterization Of Dommentioning
confidence: 99%
“…However, the FI was modified by Cory and McKnight (2005) to the ratio of em wavelengths at 470 nm and 520 nm, obtained at ex 370.…”
Section: Humic-like Componentsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been demonstrated that freshwater systems do not simply act as conduits between land and ocean, but are active zones of dissolved organic matter cycling through biological processing (Battin et al 2008(Battin et al , 2009, photodegradation (Cory et al 2007), freezing and dehydration (Hudson et al 2009), and physical processes such as colloid formation and particle settling (Battin et al 2008;Aiken et al 2011). For example, studies have shown high CO 2 degassing from large rivers (Cole and Caraco 2001).…”
Section: Introductionmentioning
confidence: 99%